Adjuvant therapy using ozonated saline in a dog with persistent thrombocytopenia - case report (Research, Society and Development, 2020)
The aim of this paper is to describe the platelet increase in a dog with persistent thrombocytopenia, when it was subjected to adjuvant ozone therapy, correlating the effects of this gas on metabolism and its cellular mobilization. Thrombocytopenia is characterized by hematological changes, with a reduction in the number of platelets in the blood. There are several diseases related to thrombocytopenia, among them we can mention hemoparasitosis, where thrombocytopenia appears as a result of megakaryocytic hypoplasia, or due to immune causes, related to the presence of antiplatelet antibodies, which cause accelerated destruction of platelets by macrophages of the phagocytic mononuclear system. Several therapies can be instituted, according to their underlying cause. However, there are few descriptions of the association of adjuvant therapies, such as the use of ozone as a therapeutic form. Ozone (O3) has been shown to be promising in medicinal use, being used in the treatment of several diseases, including those of a hematological nature, requiring further studies for its validation and scientific proof. A 10-month-old canine patient was seen with suspected hemoparasitosis, with a history of contact with ectoparasites and lack of appetite. The clinical signs observed were pale mucous membranes and epistaxis. Treatment was instituted, using doxycycline-based antibiotics, for a period of 28 days, in addition to blood transfusion and use of erythropoietin, but without success. In view of this situation, we opted for the institution of adjuvant ozone therapy, through the infusion of ozonated saline solution, intravenously. After 15 days of association, the patient improved his persistent thrombocytopenia, evidenced after new tests, as well as clinical improvement of the signs previously presented.